Agile Performance Management - Hibah Yuliana Khamila; Fithiyatul Husnah; Mochammad Isa Anshori (Institut Nalanda, 2023)
In order to improve employee performance, intervention on motivation is highly recommended. Apart from increasing the motivation of its employees, companies also need to direct their employees to have an agile performance management system. By implementing agile performance management, employees will be able to achieve the company's vision and mission, meet growing business needs and drive the company's progress. In working on this article the author used the library research method (Literaty Research), namely research activities carried out by collecting information and data with the help of various materials in the library or sources from the internet related to the problem to be solved. The data obtained comes from qualitative methods which emphasize analysis and descriptiveness with presentation not in the form of numbers.